Integrated technical problem management system (ITPMS) - Mohamad Noor, Norzaliha (2005)
The Integrated Technical Problem Management System is a system that is designed to integrate the two types of processes involved in the handling of problem management processing. The processing are the automated legacy system and the manual processing. ITPMS is an automated system which also includes the functions of problem management handling that are monitoring, escalating and controlling the problems. As an automated system, ITPMS is able to perform the creation, deletion and updating the record. In addition, the system also can supply the statistical data and information for the management.